CONCEPTUAL MODEL OF ACHIEVING COMPETITIVE ADVANTAGE (CA) THROUGH THE ROLE OF HUMAN RESOURCES MANAGEMNT (HRM) PRACTICES ON INNOVATIVE WORK BEHAVIOR (IWB) EVIDENCE IN JORDANIAN BANKS - Qawasmeh, Esraa Farid; Wahab, Norailis Abd (International Journal of Psychosocial Rehabilitation, 2020)
Maintaining Competitive Advantage (CA)faced challenges in the organizations through improving the products quality or reducing the production time and costs. To achieve CA, the employees should perform their jobs in innovative ways which can be motivated using strategies such as Human Resource Management (HRM) practices. This research propose conceptual model to construct the relationships between HRM practices, Innovative Work Behavior (IWB), and CA. The heroically considerations are reviewed to construct the conceptual model. Significantly, HRM practices include three independent dimensions; training, direct and indirect compensations, where innovative work behavior considered as mediating variable. Competitive advantage consists of four dimensions; production quality, costs, time, and flexibility. Four research hypotheses are suggested to investigate the research problem. This study recommends the implementation of the conceptual model in Jordanian banking sector, which could represent the research scope of the empirical study based on the proposed model.